Where is the Value Added? Trade Liberalization and Production Networks - Rahel Aichele; Inga Heiland (Center for Economic Studies and ifo Institute (CESifo), 2016)
Fragmentation of the global value chain makes it difficult to assess the effects of trade liberalization on the global pattern of production. Gross bilateral trade ows no longer reveal a country's or a sector's value added contribution. Yet, it is value added that matters for employment and welfare. We derive a structural equation for value added trade ows and theory-based measures for production networks from a multi-sector gravity model with inter-sectoral linkages to analyze the effects of trade liberalization in the presence of globally fragmented value chains. We estimate the model's key parameters, calibrate it to the year 2000 using the World Input-Output Database, and perform a counterfactual analysis of China's WTO accession. We find that China's WTO entry accounts for about 45% of the decrease in China's value added exports to exports ratio and for about 7% of the decline in this figure on the world level as observed between 2000 and 2007. Furthermore, our results imply that China's WTO accession was the driving force behind the strengthening of production networks with its neighbors and led to significant welfare gains for China, Australia, and the proximate Asian economies.
Keywords: F13; F14; F17; 330; structural gravity; trade in value added; tariff liberalization; production networks; China's WTO entry